An inexact restoration package for bilevel programming problems - Pilotta, Elvio Angel (2012)
Bilevel programming problems are a class of optimization problems with hierarchical structure where one of the constraints is also an optimization problem. Inexact restoration methods were introduced for solving nonlinear programming problems a few years ago. They generate a sequence of, generally, infeasible iterates with intermediate iterationsthat consist of inexactly restored points. In this paper we present a software environment for solving bilevel programming problems using an inexact restoration technique without replacing the lower level problem by its KKT optimality conditions. With this strategy we maintain the minimization structure of the lower level problem and avoid spurioussolutions. The environment is a user-friendly set of Fortran 90 modules which is easily and highly configurable. It is prepared to use two well-tested minimization solvers and different formulations in one of the minimization subproblems. We validate our implementation using a set of test problems from the literature, comparing different formulations andthe use of the minimization solvers.